A rhinocerotid-dominated megafauna at the MIS6-5 transition: The late Middle Pleistocene Coc Muoi assemblage, Lang Son province, Vietnam. (15th April 2018) - Bacon, Anne-Marie; Antoine, Pierre-Olivier; Huong, Nguyen Thi Mai; Westaway, Kira; Tuan, Nguyen Anh; Duringer, Philippe; Zhao, Jian-xin; Ponche, Jean-Luc; Dung, Sam Canh; Nghia, Truong Huu; Minh, Tran Thi; Son, Pham Thanh; et al.
Abstract: Little is known about the ecosystems in the north of the Indochinese peninsula at the Middle-Late Pleistocene transition. In this paper, we analyzed the new fauna from Coc Muoi cave, Lang Son province, northeast Vietnam. In comparison with other well-documented faunas from the region, that of Coc Muoi is distinguished by the predominance of rhinoceroses among diverse large-bodied herbivores. The results of the OSL and pIR-IRSL dating of the cave sediments and U-series dating of flowstones indicate a potential age range of 148-117 ka for the fauna (MIS6-5). The analysis of age-at-death distributions of rhinoceroses, wild cattle, sambar deer, and wild pig, does not show any apparent selectivity of age classes. We also focused our study on rhinoceroses, tapirs, and wild cattle by analyzing the prevalence of hypoplastic defects on deciduous and permanent teeth, in an attempt to assess the health status of the taxa during their first years of growth. The health status of large-bodied herbivores (kouprey and rhinoceros) reveals the importance of stressors (biotic and abiotic) in the rainforest environment during a period of marked climatic transition (MIS6-5) in comparison with other MIS5-4 well-documented faunas from the region. Highlights: Coc Muoi cave is located in Lang Son province, north east Vietnam. The site produced a Rhinoceros sondaicus -dominated fauna. The age estimate of the fauna (SG-OSL and pIR-IRSL) is 148-117 ka (MIS6-5). Tigers had access to a large spectrum of megaherbivores in rainforests. Prevalence of enamel hypoplasia reveals the importance of stressors in rhinoceroses.